Monitoring training loads in ice hockey - Horowitz, M. (2014)
Historically, the ability of coaches to prescribe training to achieve optimal athletic performance can be attributed to many years of personal experience. A more modern approach is to adopt scientific methods in the development of optimal training programs, however modern methods have yet to be adopted in ice hockey. Currently, session Rating of Perceived Exertion (sRPE) is the sole method validated to be able to quantify TL in the team sport setting, and thus it can be applied in ice hockey. The study applied sRPE in ice hockey aiming to (1) investigate to what degree of accu-racy the participating collegian ice hockey team`s coaching staffs were able to implement pre-planned periodized schedules; and (2) to investigate loading patterns of individuals and segments constructing the team. Firstly, sRPE was introduced by mean of presenting research data validating the use of this method in sports similar to ice hockey. Secondly, training loads encountered by 19 women, collegian, USA Division 1 ice hockey players were measured using sRPE and an analyses of loads distribution and training implementations was performed. Results demonstrated significant differences between the coaches intended periodized training program and the program experienced by the players. Additionally, segmenting the team revealed meaningfully different load distributions between positions and between players of different experience level. Finally, each player experienced significantly different loading patterns as well. The article confirms sRPE to be a valuable tool in ice hockey and load monitoring to be more accurate when the team is segmented to groups and as individual players.